(untitled) (Pharmacy Essentials: A Compact Guide for Students and Practitioners, 2025)
Author Dr. Ramesh Kumar Gupta, Associate Professor, Department of Pharmacology, Amity Institute of Pharmacy, Amity University, Lucknow, Uttar Pradesh, India Abstract Pharmacology explains how drugs produce therapeutic and adverse effects through their interactions with biological systems. Pharmacodynamics reveals the molecular mechanisms of drug action, with receptor theory explaining how medications interact with specific cellular targets through agonist, antagonist, and modulator relationships, producing dose-dependent responses that can be quantified through key parameters describing potency and efficacy. Pharmacokinetic processes of absorption, distribution, metabolism and excretion determine drug concentration at target sites, with mathematical models describing drug movement throughout the body, enabling prediction of appropriate dosing regimens and explaining variability in drug response across different patient populations. Drug-drug interactions occur through pharmacokinetic mechanisms altering drug concentrations or pharmacodynamic processes modifying responses without changing concentrations, with clinical significance determined by therapeutic index, interaction magnitude, and patient-specific risk factors requiring systematic management strategies. Adverse drug reactions range from predictable, dose-dependent extensions of pharmacological effects to unpredictable idiosyncratic responses, with detection, assessment, and preventive measures focusing on risk factor identification, monitoring programs, and reporting systems contributing to medication safety Keywords: Receptor; Mechanisms; Drug Disposition; Therapeutic Response; Medication Safety; Physiological Effects VIEW PDF